2003
DOI: 10.1021/jo0344945
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Supported Synthesis of Cryptand-like Macrobicyclic Peptides

Abstract: A straightforward method for the solid-supported synthesis of cryptand-like bicyclic peptides (1-5) on a backbone amide linker has been described. For the branching, two novel easily available building blocks, viz. N-(4-methoxytrityl)-N-(2-nitrobenzenesulfonyl)-protected N,N-bis(2-aminoethyl)-beta-alanine (6) and N-(9-fluorenylmethoxycarbonyl) protected iminodiacetic acid monoallyl ester (7), have been employed. The key steps of the synthesis are as follows: (i) stepwise coupling of one amino acid and 6 to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Because of their relatively large sizes and ability to make multiple points of contact with a flat surface, macrocycles effectively compete with proteins for binding to flat surfaces and yet retain many of the pharmacokinetic properties of small molecules such as membrane permeability. Compared to protein drugs, macrocycles have greater metabolic stability, less likelihood of eliciting an immune response, and lower cost of production. To further rigidify the structures and improve the binding affinity/specificity and metabolic stability, bicyclic peptides and peptoids have also been generated. Since rational design of macrocyclic inhibitors against PPIs is difficult, a popular approach has involved synthesizing and screening large libraries of bicyclic peptides and peptoids. To date, bicyclic peptide libraries have only been synthesized ribosomally by phage or mRNA display and are largely limited to proteinogenic amino acids (and certain unnatural α- l -amino acids) as building blocks. …”
Section: Introductionmentioning
confidence: 99%
“…Because of their relatively large sizes and ability to make multiple points of contact with a flat surface, macrocycles effectively compete with proteins for binding to flat surfaces and yet retain many of the pharmacokinetic properties of small molecules such as membrane permeability. Compared to protein drugs, macrocycles have greater metabolic stability, less likelihood of eliciting an immune response, and lower cost of production. To further rigidify the structures and improve the binding affinity/specificity and metabolic stability, bicyclic peptides and peptoids have also been generated. Since rational design of macrocyclic inhibitors against PPIs is difficult, a popular approach has involved synthesizing and screening large libraries of bicyclic peptides and peptoids. To date, bicyclic peptide libraries have only been synthesized ribosomally by phage or mRNA display and are largely limited to proteinogenic amino acids (and certain unnatural α- l -amino acids) as building blocks. …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Selective molecular recognition 6,7 and signalling [8][9][10][11][12] properties are sought to provide the major impetus for further progress in this flourishing area of chemistry, while various applications in biochemistry and medicine, catalysis, or material sciences have already opened new horizons for the utilization of this class of compounds. [13][14][15][16][17] In this respect, conformationally constrained bicyclic polyamines with bridgehead nitrogen atoms have gained increasing attention over the last three decades because the additional rigidity provided by strapping the macrocyclic framework imparts intriguing anion- 18 and metal-binding properties. 19 Contemporary to the disclosure of the first cryptands by Lehn's group, 2,3 Simmons and Park showed that protonation of diazabicyclo[k,l,m]alkanes of various sizes [6 r (k,l,m) r 10] occurs outside the cavity in the initial stage, while the inversion of the ammonium nitrogen atom is in the hour time range.…”
Section: Introductionmentioning
confidence: 99%
“…Virta and Lo ¨nnberg applied the monoalkoxybenzaldehyde linker for the solid-phase synthesis of macrocyclic cryptantlike peptides and released the substrates from the resin by utilizing a mixture of HBr, AcOH, and TFA mixed with anisole as a scavenger (synthesis further discussed under section 3.2.4). 40 Brandt et al demonstrated release of a pentapeptide in good yield from a monoalkoxy BAL by a 2 h treatment with TFMSA-TFA (1:9) at room temperature. 41 In an alternative design of a slightly more acid-labile monoalkoxybenzyl BAL, Gu and Silverman introduced the alkyl spacer directly to the aromatic core of 4-methoxybenzaldehyde via carbon-carbon formation.…”
Section: Mono-and Dialkoxybenzyl Balmentioning
confidence: 99%